Influence of Antenatal Care 10T to the Statisfaction of Pregnant Maternal in Asyifa Clinic Meurah Dua Sub-District Pidie Jaya Regency - Wahyuni Wahyuni; Samsidar Sitorus; Aida Fitria (PSPP JOURNALS, 2021)
The policy of Health Departmentin an effort to accelerate the reduction in Maternal Mortality Rate (MMR) and under-five Mortality rate (IMR) basically refers to the strategic intervention “the Four Pillars of the Safe Motherhood” (Family Planning, Antenatal Care,childbirth and Obstetric care Essential). Coverage K4 indonesia (2006 – 2018), the coverage of health services for expectant mothers K4 tend to increase. This study aimed to analyze the influence of antenatal care 10T to the satisfaction of pregnant women in the Clinic Asyifa Kecamatan Meurah Dua Pidie Jaya District.This stuay was a quantitaive with quasy experiment. It was conducted in Asyifa Clinic, Meurah Dua Sub-District Pidie Jaya District. The population was 20 respondents. The sample of this study was taken from all tottal population. Data were analyzed by using Wilcoxon Signed Rank Test.The result showed before intervention 10T, the number of satisfying and disatisfying of mothers of 10 respondents (50.0%). But after intervention 10T, the mother who satisfied increased to17 respondents (85.0%), and 3 (15.0%) respondents were dissatisfied. It was found influencing of Antenatal Care 10T to satisfying of maternal with p-value 0.000.The conclusion drowned the influence of antenatal care 10T to the satisfaction of pregnant women in the clinic Asyifa District MuerahDua Pidie Jaya District in 2019. It is suggested to health services can be a reference for improving the quality of service and degree of public health associated with the service of the ANC is better by applying standard 10T.